The corrosion response of the heterogeneous nitriding structure originated from the laser additive manufactured steel. (1st July 2023) - Hong, Y.; Dong, D.D.; Zou, G.P.; Li, Y.; Lin, S.S.; Kuang, T.C.; Wu, Y.Z.; Dai, M.J.
Abstract: Corrosion of the laser additive manufactured (LAM) steel attracts increasing attentions. In this work, plasma nitriding was carried out to improve the strength and corrosion resistance of LAM 18Ni300 maraging steel at the same time. Nitriding of the as-fabricated sample obtains a heterogeneous nitriding structure with typical LAM dendrite boundaries. Nanosized N-rich grains and associated N-depleted grains were found along the LAM dendrite boundaries, which are beneficial for pitting resistance. Moreover, the corrosion reaction of the nitrided surface is confirmed as γ′/γ + O → MeO(N) + Me +, (Me = Fe, Co, Ni, Mo). Graphical Abstract: ga1 Highlights: Corrosion resistance of LAM maraging steel are improved by two nitriding structures. Corrosion responses of the two nitriding structures are different. LAM dendrite boundaries are beneficial for pitting resistance of nitrided surface. The corrosion reactions of nitrides are confirmed by HRTEM.